Mobility, Equity and Sustainability Today in Tirana - Pojani, Dorina (TeMA - Journal of Land Use, Mobility and Environment, 2011)
This article discusses the development of transport inequalities in Tirana during its rapid population and economic growth since the fall of communism in 1990. The first part provides background on the development of Tirana and its urban travel systems, in an effort to take a step towards filling the research void on this city. Tirana’s case is particularly interesting because during communism private car ownership was prohibited and there were virtually no cars on the streets. Subsequently, when the population acquired wealth and personal freedom, the city grew substantially in all directions and was invaded by car traffic. The second part of this article analyses the findings of recent transportation surveys, conducted by this author, with a focus on the transport disadvantage that women, children, the poor, the elderly, and the handicapped experience. This discussion is preceded by a brief review of studies reflecting the emergence of concerns about transport inequality issues in other European nations during the past few decades. The article concludes with policy recommendations based on public opinions on transport issues, collected through the author’s surveys.